Australia Day, flags on cars and Australian nationalism - Fozdar, F.; Spittles, B.; Hartley, Lisa (SAGE, 2014)
This article reports the results of research into the recent popular phenomenon of flying Australian flags on one’s car for Australia Day. A survey was undertaken in Western Australia in 2011 to ascertain who flies the flag and why. Results indicate the phenomenon was widespread, with a quarter of those surveyed displaying car-flags. A clear relationship between car-flag-flying and exclusionary nationalism is demonstrated. Car-flag-flyers rate more highly on measures of patriotism and nationalism, and feel more negative towards Muslims and asylum seekers, and more positive about the White Australia Policy. They are also significantly more likely to feel their culture and values are in danger, and have a nativist vision of Australian identity. While both groups are positive about Australia’s diversity, car-flag-flyers are more likely to feel that migrants should assimilate. The results support other literature that suggests that in some contexts the Australian flag has come to be associated with exclusionary nationalism.